Nemo-like kinase 1 (Nlk1) and paraxial protocadherin (PAPC) cooperatively control Xenopus gastrulation through regulation of Wnt/planar cell polarity (PCP) signaling - Kumar, Rahul; Ciprianidis, Anja; Theiß, Susanne; Steinbeisser, Herbert; Kaufmann, Lilian (Differentiation, 2017)
The Wnt/planar cell polarity (PCP) pathway directs cell migration during vertebrate gastrulation and is essential for proper embryonic development. Paraxial protocadherin (PAPC, Gene Symbol pcdh8.2) is an important activator of Wnt/PCP signaling during Xenopus gastrulation, but how PAPC activity is controlled is incompletely understood. Here we show that Nemo-like kinase 1 (Nlk1), an atypical mitogen-activated protein (MAP) kinase, physically associates with the C-terminus of PAPC. This interaction mutually stabilizes both proteins by inhibiting polyubiquitination. The Nlk1 mediated stabilization of PAPC is essential for Wnt/PCP signaling, tissue separation and gastrulation movements. We identified two conserved putative phosphorylation sites in the PAPC C-terminus that are critical for Nlk1 mediated PAPC stabilization and Wnt/PCP regulation. Intriguingly, the kinase activity of Nlk1 itself was not essential for its cooperation with PAPC, suggesting an indirect regulation for example by impeding a different kinase that promotes protein degradation. Overall these results outline a novel, kinase independent role of Nlk1, wherein Nlk1 regulates PAPC stabilization and thereby controls gastrulation movements and Wnt/PCP signaling during development.